An age-structured virus model with two routes of infection in heterogeneous environments. (February 2018) - Cheng, Chang-Yuan; Dong, Yueping; Takeuchi, Yasuhiro
Abstract: On the basis of the complexity of the human body, we explore viral dynamics by using a two-compartment model incorporating the age since infection of infected cells and both virus-to-cell infection and cell-to-cell transmission routes. The basic reproduction number, R 0, of the system is formulated from two mechanisms: one is the potential trigger from a single infection route in a compartment and the other is the synergistic effect of a viral infection in two compartments. Accordingly, we prove that the infection-free equilibrium is globally asymptotically stable (GAS) if R 0 < 1, whereas virus persists uniformly with respect to the initial infection if R 0 > 1 . From the viewpoint of a predominant infection route incorporated with another mild infection route, we demonstrate global convergence to the infected equilibrium by applying a theory of perturbation on the globally stable steady state.